Evaluating Long‐Term Outcomes of Children Undergoing Surgical Treatment for Congenital Heart Disease for National Audit in England and Wales - Kate L. Brown; Qi Huang; Ferran Espuny‐Pujol; Julie A. Taylor; Jo Wray; Carin van Doorn; Serban Stoica; Christina Pagel; Rodney C. G. Franklin; Sonya Crowe (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background There is strong interest in the evaluation of longer‐term outcome metrics for congenital heart diseases (CHDs); however, registries focus on postoperative metrics. Methods and Results Informed by user online discussion forums and scoping of national data, we selected sentinel CHDs and long‐term outcome metrics suitable for routine monitoring. We then developed sentinel CHD phenotypes and algorithms for identifying treatment pathway procedures using clinical codes. Finally, we calculated the metrics within a retrospective national cohort analysis. The 9 selected sentinel CHDs had a higher‐than‐average prevalence, typically involved surgery in infancy, and were associated with an increased risk of late mortality. The selected metrics of survival and reinterventions at 1, 5, and 10 years were both important and feasible. The cohort included 29 319 (41.3% of all operated CHD births) English and Welsh children born with sentinel CHDs in 2000 to 2022. Example metrics at age 10 years included: survival—hypoplastic left heart syndrome: 57.6% (95% CI, 54.9%–60.4%), functionally univentricular heart: 86.7% (95% CI, 84.6%–88.9%), transposition of the great arteries: 93.1% (95% CI, 92.2%–93.9%), pulmonary atresia: 81.0% (95% CI, 79.1%–82.9%), atrioventricular septal defect: 88.5% (95% CI, 87.5%–89.5%), tetralogy of Fallot: 95.1% (95% CI, 94.4%–95.8%), aortic stenosis: 94.4% (95% CI, 93.3%–95.6%), coarctation: 96.7% (95% CI, 96.2%–97.3%), and ventricular septal defect: 96.9% 95% CI, (96.4%–97.3%); and (2) cumulative incidence of reintervention—hypoplastic left heart syndrome : 54.5% (95% CI, 51.5%–57.3%), functionally univentricular heart: 57.3% (95% CI, 53.9%–60.5%), transposition of the great arteries: 20.9% (95% CI, 19.5%–22.3%), pulmonary atresia: 66.8% (95% CI, 64.2%–69.1%), atrioventricular septal defect: 21.6% (20.3%–23.0%), tetralogy of Fallot: 26.6% (95% CI, 25.2%–28.0%), aortic stenosis: 31.2% (95% CI, 28.8%–33.6%), coarctation: 19.8% (95% CI, 18.6%–21.1%), and ventricular septal defect: 6.1% (95% CI, 5.5%–6.8%). Conclusions It is feasible to report important long‐term outcomes of survival and reintervention for sentinel CHDs using routinely collected procedure records, adding value to national audit.